Enhancing supply chain performance through collaborative planning, forecasting, and replenishment. Issue 4 (3rd July 2019) - Singhry, Hassan Barau; Abd Rahman, Azmawani
Abstract : Purpose: Despite the importance of collaborative planning, forecasting, and replenishment (CPFR), its influence on supply chain innovation capability (SCIC) and supply chain performance (SCP) has not been sufficiently examined. The purpose of this paper is to examine the antecedence of SCP through CPFR and SCIC. Design/methodology/approach: Through cluster and stratified random sampling, 286 responses from top managers of 1, 574 Nigerian manufacturing companies were analyzed. Data analysis was performed using structural equation modeling with AMOS graphics. Findings: The results show that SCIC has a full mediating effect on the relationship between CPFR and SCP. Specifically, CPFR has a significant relationship with both SCP and SCIC, and SCIC also relates significantly to SCP. Practical implications: This study offers implications for manufacturers in developing countries in general, and in Nigeria in particular, by providing a guideline on how to improve SCP through CPFR. Originality/value: The paper contributes to the limited studies on CPFR and SCP by extending this line of study into the realm of innovation capability and innovation. It integrates the social exchange theory and the dynamic capabilities theory to examine the collaborative processes of CPFR in the supply chain context. This study stressed the importance of boundary theoretical spanning by extending CPFR and SCP into the domain of innovation capability.